Experimental and computational fluid dynamics investigation on the performance of leakage sensor model - Al-Qahtani, Turki S A H (2021)
Water is an extremely important natural resource and fresh water management need to be handled in a systematic and efficient way so that fresh water supply always sufficient for the ever-growing population. In the Arabian Gulf, the scarcity of fresh water causes the authority to use the desalination technology to convert the salt water into water that suitable for the human consumption. This technology comes with a high cost and it is important to detect pipe leakage to avoid wastage of the water. Hence, the current work aim is to propose a new leakage detector shape and analyse the performance using CFD simulation and an experimental work. Mobility module of Design 4 has been designed and developed base on the aerodynamics performance of the earlier design mobility module. The design hydrodynamics performance also been investigated via experimental work and it has a preferable performance when simulated in the real pipe condition to detect leakage in the pipeline. Design optimization has been carried out to further improve the performance of the mobility module to be working in the real pipe condition. The basic shape is fixed as the same as the mobility module that has been chosen in the previous comparison. The design hydrodynamics performance also been investigated via CFD simulation. Data from simulation analysis has shown that the determination of domain locations affected the numerical calculation results. Identification of mesh size and mesh type will produce accurate results such as implementation of refining mesh focusing on potential turbulent flow area will obtain more smoothness results. The selection of a proper turbulent model also will influent the result. Finally, the design performance been assessed via parametric study. The parametric study shows the effects of upstream velocity and model design on the variation of drag force. Based on the comparisons between the results obtained through numerical analysis, it can be concluded that the drag force of leakage sensor increases direct proportionally with the upstream flow velocity. There is no significant different between modified design 1 and design 2 in the simulation procedure but both results are 3 times higher than original best design which is 300% improvement from experimental procedure in all upstream velocity.